The Urgency Of Ratifying The Elimination Of Sexual Violence Draft Bill In The Perspective Of Criminal Law - Ismail, Audaraziq; Zulfa, Eva Achjani; Yulianti, Lulu; Anggara, Matius Evan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Regulations on sexual violence or violence are scattered in several regulations in Indonesia. However, along with the rapid and massive technological development, new form of criminal offenses related to sexual violence have emerged which have not been accommodated in the statutory regulations. Too many regulations related to sexual violence also create new problems, specifically overcriminalization, overlapping, and the lack of coordination and systematic fulfillment of the protection for the rights of victims of violence by authorized institutions. These problems are the fundamental why the elimination of sexual violence draft bill should be ratified immediately. Based on the reasons above, the elimination of sexual violence draft bill is interesting to analyze. This research was conducted with a statutory approach and an analytical approach using relevant legal concepts and theories. Criminal offenses related to sexual violence are regulated in several regulations, the Criminal Code, the PKDRT Law, the TPPO Law, the ITE Law, the Child Protection Law and the Pornography Law. However the law that exist are not comprehensive yet for the expansion of criminal offenses for violence and fulfillment of the rights of victims who are not the subject according to the law, as well as the issue of overregulation becomes the urgency whyelimination of sexual violence draft bill should be ratified immediately.Regulations on sexual violence or violence are scattered in several regulations in Indonesia. However, along with the rapid and massive technological development, new form of criminal offenses related to sexual violence have emerged which have not been accommodated in the statutory regulations. Too many regulations related to sexual violence also create new problems, specifically overcriminalization, overlapping, and the lack of coordination and systematic fulfillment of the protection for the rights of victims of violence by authorized institutions. These problems are the fundamental why the elimination of sexual violence draft bill should be ratified immediately. Based on the reasons above, the elimination of sexual violence draft bill is interesting to analyze. This research was conducted with a statutory approach and an analytical approach using relevant legal concepts and theories. Criminal offenses related to sexual violence are regulated in several regulations, the Criminal Code, the PKDRT Law, the TPPO Law, the ITE Law, the Child Protection Law and the Pornography Law. However the law that exist are not comprehensive yet for the expansion of criminal offenses for violence and fulfillment of the rights of victims who are not the subject according to the law, as well as the issue of overregulation becomes the urgency whyelimination of sexual violence draft bill should be ratified immediately.